Contracts, structures, and computation mechanisms of Islamic bank retail financing products: a critical assessment - Saiti, Buerhan; Abdul Wahab, Hishamuddin; Ahmad, Khaliq (Palgrave Macmillan, 2017)
This chapter discusses Islamic bank retail financing, its instruments, and operations. The discussion demonstrates that it is essential to have a banking system based on Shariah principles that fulfill the needs of Muslim consumers. The chapter examines the various personal financing products, their underlying Islamic contracts, and their computational mechanisms with appropriate examples. It also critically evaluates the products of Islamic bank retail financing. The availability of various personal financing instruments in Islamic banks allows Muslim consumers to achieve their financing needs. Moving forward, a greater variety of instruments that invite fewer Shariah issues must be offered in the market to ensure a more vibrant Islamic banking system.